Synthesis of arylated norbornyl amino acid esters - Gunkara, Omer Tahir; Kulu, Irem; Ocal, Nuket; Kaufmann, Dieter E. (SPRINGER WIEN, 2010)
Palladium-catalyzed hydroarylation of optically active norbornenimide-protected amino acid esters was studied to stereoselectively synthesize a series of new exo-aryl(hetaryl)-substituted norbornyl amino acid methyl esters.
Keywords: Amino acids; Aromaticity; C-C coupling; Homogeneous catalysis; Heterocycles; DOMINO-HECK REACTIONS; EPIBATIDINE; CHEMISTRY; IMIDES